Efektivitas Penerapan Restorative Justice dalam Menyelesaikan Kasus Tindak Pidana Di Wilayah Hukum Polres Puncak Jaya - Dedy Syahputra Bintang (Ridwan Institute, 2021)
Restorative justice has been used by the Puncak Jaya Resort Police (Polres) in a number of criminal cases that happened within the Puncak Jaya Police's jurisdiction. This is because if a case is not settled by customary law, the Puncak Jaya community is often dissatisfied. Positive legislation is thought to be less sensitive to the needs of the society when it comes to criminal proceedings. The Puncak Jaya Police Department uses a restorative justice approach to mitigate the occurrence of new issues that could arise as a result of aggrieved parties' frustration. This study is a normative legal study that was performed using qualitative approaches and secondary data sources. The data is gathered from reliable sources based on literature reviews. In an inductive method, where research is conducted from general to more specific topics, conclusions are drawn from the research. The restorative justice strategy can be considered a viable option for resolving criminal cases in Puncak Jaya. This is because, in some circumstances, the restorative justice approach is a form of settlement that can satisfy the wishes of the parties concerned. In order for the matter to be settled according to the desires of the parties concerned. The Puncak Jaya community's customary law includes the payment of customary fines as one form of punishment. Customary fines are intended to compensate the victim for the harm caused by the perpetrator's criminal act. As a result, any customary fines that all parties have settled upon must be charged. he customary law payment is made at the police department in front of prosecutors and other interested parties.